Atmospheric-pressure-plasma-jet processed carbon nanotube (CNT)–reduced graphene oxide (rGO) nanocomposites for gel-electrolyte supercapacitors. Issue 6 (12th January 2018) - Kuok, Fei-Hong; Chien, Hung-Hua; Lee, Chia-Chun; Hao, Yu-Chuan; Yu, Ing-Song; Hsu, Cheng-Che; Cheng, I-Chun; Chen, Jian-Zhang
Abstract : This study demonstrates ultrafast (15 s) atmospheric-pressure-plasma-jet (APPJ) processed CNT–rGO nanocomposite gel-electrolyte supercapacitors. Abstract : This study evaluates DC-pulse nitrogen atmospheric-pressure-plasma-jet processed carbon nanotube (CNT)–reduced graphene oxide (rGO) nanocomposites for gel-electrolyte supercapacitor applications. X-ray photoelectron spectroscopy (XPS) indicates decreased oxygen content (mainly, C–O bonding content) after nitrogen APPJ processing owing to the oxidation and vaporization of ethyl cellulose. Nitrogen APPJ processing introduces nitrogen doping and improves the hydrophilicity of the CNT–rGO nanocomposites. Raman analysis indicates that nitrogen APPJ processing introduces defects and/or surface functional groups on the nanocomposites. The processed CNT–rGO nanocomposites on carbon cloth are applied to the electrodes of H2 SO4 –polyvinyl alcohol (PVA) gel-electrolyte supercapacitors. The best achieved specific (areal) capacitance is 93.1 F g −1 (9.1 mF cm −2 ) with 15 s APPJ-processed CNT–rGO nanocomposite electrodes, as evaluated by cyclic voltammetry under a potential scan rate of 2 mV s −1 . The addition of rGOs in CNTs in the nanoporous electrodes improves the supercapacitor performance.